Exploring the Shifting Motivations for Counter-Urbanization Moves: A Comparative Analysis - Tesařová, Šárka; Jeřábek, Hynek (Lidé města, 2025)
Building upon Peter Rossi’s foundational research on migration motivations in the 1950s, this study examines the main reasons for counterurbanization moves. Rossi, employing the reason analysis methodology pioneered by Paul Felix Lazarsfeld, identified core factors influencing relocation decisions. We utilize a similar approach, adapted to the contemporary context, to explore the composition of motives for counterurbanization movements and compare Rossi’s findings with data collected in recent years. This comparative analysis sheds light on how the main motives for relocation have changed over time. The research explores the factors driving individuals to pursue lifestyle changes through migration, analysing the relative importance of various motivations in the current landscape. While our findings suggest that core factors like physical space (size) and home ownership remain relevant, the social environment holds a different significance today. Unlike the past focus on the social status of neighbours, contemporary lifestyle migrants prioritize how a location aligns with their occupational and leisure pursuits. Hobbies, which often contribute to household income, now factor into the social environment equation, shaping the desired community characteristics. By examining historical and contemporary trends, this study reveals the evolving nature of human mobility and the factors shaping people’s decisions to relocate for improved quality of life.